If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(r + -6) = -70 Reorder the terms: -10(-6 + r) = -70 (-6 * -10 + r * -10) = -70 (60 + -10r) = -70 Solving 60 + -10r = -70 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -10r = -70 + -60 Combine like terms: 60 + -60 = 0 0 + -10r = -70 + -60 -10r = -70 + -60 Combine like terms: -70 + -60 = -130 -10r = -130 Divide each side by '-10'. r = 13 Simplifying r = 13
| -6(-10+p)=24 | | logx(18)=6 | | -5.2-4z-1.9-2z=-5z+0.1 | | -4+12n=-256 | | 8-(4z-9)=2-5z | | 16=-2w+9 | | x+9*9= | | a=(6-4)/(2-1) | | -14.5+-1.5= | | 2(z-9)-(4z-7)=-3z | | -14.5+1.5= | | 9-4x-5-11x=7 | | -6a-6=-36 | | g(-9)=2x^2-8x | | -3(6+k)=-87 | | (2-j)*(3+5j)=0 | | 11(2+x)=231 | | -0.3x+8.93=-0.5x+4.33 | | 2x+5*2x= | | 4y=-x+-16 | | 1/9÷1/3 | | 3r-1=-37 | | a^5+4=14 | | -5x+49x=21x+53 | | 12x^3-12x=y | | Y=5A+B | | x/4+3=3.5 | | 5+10=-13+x | | 10=5(4R)+5R | | 8x-19=6x+9 | | 1/2^2 | | -13-19(b-17)=-18(b-16)-14 |